Segregação espacial e acessibilidade urbana: uma análise municipal de adaptação de praças - Borges, Ana Gabriela Rigo (2021)
This research aims to understand the parameters of the degree of inclusion of municipal public squares, in the face of an analysis based on relevant criteria and current laws, having the city of Cascavel/PR as a case study. Considering principles of social inclusion and population welfare state, and understanding such achievements in the economic, urban and social scope. This theoretical foundation has a qualitative-quantitative approach and bibliographic research. It is considered that from this theoretical basis it is intended to take the research forward by providing the feasibility of applying a relevant to assess municipal squares, maximizing the allocation of public resources to infrastructure. It was found that the accessibility analyzes under legal and constitutional principles collaborate for public administrations to qualify and direct their investments in new or adaptations of public spaces correctly, in addition to enabling a lower degree of segregation of public investments within the urban space , providing public squares that are much less segregated and more inclusive throughout the urban perimeter.